Impact of parenting style and upbringing on menstrual stress in adolescent South Indian girls - Vijay, Christy; Ramesh, Naveen; Gonsalves, Kavita Peter (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: School absenteeism because of major symptoms like dysmenorrhea has ranged from 14% to 51% and this has affected the participation of school going girls in school related activities. In developing countries, adolescent girls face health issues due to socio-economic, environmental conditions and gender discrimination. The parenting style has been explained by Baumrind, which harbours a particular coping mechanism. This study aimed to determine the level of stress in adolescent girls during menstruation using one of these standardised scales. Objective of this study was to assess stress levels during menstrual period among adolescent girls, problems faced during menstrual period and parenting skill effect on menstrual stress. Methods: This was a cross sectional study done on adolescent girls 13 to 19 years of age. The tool used in this study included demographic details, parenting style, (PSDQ scale), prevalence of stress (PSS). All the adolescent girls aged 13-19 years. Results: The study participants 54 (24.9%) felt stressed during the days of the menstrual period, 186 (85.7%) regarded their mother as the major source for menstruation related health issues, 112 (49.3%) did not get support from their family during the time of the menstrual period. Girls with parents who are very authoritarian 28 (31.5%) and very involved 34 (34%), had stress during the menstrual period. Conclusions: Parents play a very important role during the growing phase of an adolescent girl. The communication between parents and children related to menstrual health issues is dependent on educational status of the parents and their knowledge about menstrual health.